Optimalisasi Ruang Terbuka Sebagai Ruang Produktif Bersama di Lingkungan Perumahan di Kelurahan Romang Lompoa Kecamatan Bontomarannu Kabupaten Gowa - Samsuddin Amin; Idawarni Asmal; Yahya Sirajuddin; Edward Syarif; Baharuddin Hamzah; Nurul Jamala; Asniawaty Kusno; M. Syavir Latif; Syarif Beddu (Faculty of Engineering UNHAS, 2022)
Open open space is one of the elements of space that has a function as a social binder for the resident community in a certain area, can be accessed from anywhere and anytime so that it has a sustainability function that can improve the quality of life of the community both in social, economic, and even cultural contexts. On an urban scale, the rules regarding open space are directed at efforts to achieve good oxygen conditions which are a requirement in improving the health status of the community. In residential areas, the performance of open space is more emphasized on socio-cultural functions where people can gather in a friendly atmosphere so that the optimization of open space functions in the aspect of joint economic improvement is actually open for development. Open space in a residential area in Romang Lompoa Village has the potential in the form of a large volume. The main problem lies in the lack of facilities to support community activities in developing interactive activities between fellow settlers in a social context. The purpose of this community service activity is to improve the function of the existing open space by providing the design of supporting facilities for interactive activities which can then be realized by the community in the residential environment through participatory activities based on mutual cooperation. The method of carrying out the activities formulated by the Community Service Team of the Department of Architecture, Faculty of Engineering, Hasanuddin University refers to the health protocol rules as part of efforts to break the spread of the Covid-19 Virus. Therefore, the form of activity is mostly carried out in the form of observation and evaluation of existing open spaces as well as limited interviews with stakeholders at locations at community service locations.